Dampak Model Quantum Learning terhadap Kemampuan Berpikir Kritis pada Materi Sistem Indra - Endang Hardi; Romdah Romansyah (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
Learning is a process carried out by teachers with their students. In the field, it often occurs rigidly in its implementation and is Teacher Centered so that students are less active in learning activities. The purpose of the study was to determine the impact of the Quantum Learning model on students' critical thinking skills in Class XI IPA 1 MA-Al-Kausar Banjar on the subject of the sensory system. The research time was April 13, 2025. The method used in this study was quasi-experimental. With data collection techniques through pretest and posttest with students with a sample size of 20 people. Based on the results of data analysis using the Z test, it was obtained that Zhitung = 3 and Z Tabel = 2.33, then Zhitung> Z Tabel, meaning that the impact of implementing the Quantum Learning learning model has an effect on students' critical thinking skills on the Sensory System material by 0.74 (high category).